Facies Implication of GERCUS Formation with The Bathymetry and Tectonic Activity of Van-Pyrenean Phases in Haibat-Sultan Mountain, Iraqi Kurdistan Region - Tavan Mohammed Hama Salih; Ali Mahmood Surdashy; Hemin Muhammad Hama Salih; Mushir Mustafa Baziany (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The Eocene red clastic strata are represented by molasses facies of Gercus Formation and well exposed at Haibat-Sultan Mountain . A sequence of about 88m thick of the formation is located in the middle part of the Mountain. Detailed investigations including field, petrographic investigations which are linked between bathymetric fluctuation and depositional environment. The sequence is generally found to be a shallowing upward facies which start from deep marine (Kolosh Formation) to continental environment passing through shallow marine. Petrographic studies revealed the presence of a high rate of terrigenous grains; the most abundant clasts are sedimentary rock fragments such as limestone and chert. There are less abundant clasts derived from igneous and metamorphic rocks like quartz, feldspar, and micain addition to authigenic grains of glauconite are also represented. The pore space between grains are filled by red clay with carbonate cement. The provenance consisted mainly of Balambo,Tanjiro,Shiranish,and Aqra Formations while the Igneous and metamorphic grains are reworked from ophiolte and metamorphic ource areas that cropped out on the Hinterland near Iraq-Iran border. Gercus Formation in this area is deposited in four depositional environments: fluviatile environments( river environment ), alluvial fan (shore line) , delta, and shore face environments. The deposition and fluctuation influenced by paleo-slope and regional tectonism of Van–Pyrenean phases. The Middle Part of this Formation interfingers with the Avanah Formation (Carbonate Rocks) which was deposited during the rising of sea level.